Coastal Waste Management Strategies to Preserve the Sea and Strengthen Fishing Family Economies in Tapanuli Tengah - Husnul Yaqin Harahap; Tirta Anugerah; Fitri Rahmayani Tambunan; Shofian Nanda Adiprayoga (International Journal of Marine Engineering Innovation and Research, 2025)
The potential of marine, fisheries, and tourism resources in Tapanuli Tengah Regency is increasingly threatened by the growing accumulation of unmanaged waste. Piled-up waste in coastal settlements, mangrove forest areas, and marine waters has caused severe degradation of coastal ecosystems and a decline in environmental quality. This study aims to identify the types of waste found in the coastal and marine areas of Tapanuli Tengah Regency and to formulate relevant waste management strategies to preserve the marine environment while improving the economy of fishing households. This research employs a case study method with qualitative descriptive analysis and SWOT analysis. The findings indicate that inorganic waste—particularly plastic—dominates the coastal and marine areas, followed by styrofoam, baby diapers, and fabric waste. These types of waste were found accumulating at the research locations: Mela I Village, Pondok Batu Village, Hajoran Village, and Jago-Jago Village. Based on the SWOT analysis, several recommended waste management strategies include environmental awareness and education programs for coastal communities, the development of facilities for sorting organic and inorganic waste, the establishment of Waste Banks at the village or sub-district level, the development of handicrafts made from plastic waste, composting of organic waste, and regular community-led “clean and waste-free sea” activities initiated by the local government and residents. These strategies are expected to support marine conservation and strengthen the economic resilience of fishing families.